Based on big data of computer room monitoring and forecasting for Intelligent analysis - Liu, Shan; Liu, Lu; Yang, Hua; Yue, Keming; Guo, Ting (2020 IEEE 5th Information Technology and Mechatronics Engineering Conference (ITOEC), 2020)
With the rapid development of the Internet, the demand for electric power industry of our country has showed a trend of rising year by year, the construction scale and volume has been expanding, involving the number of servers is numerous, equipment management difficulty increases, therefore, how to avoid the happening of server equipment failure has become an important subject in power system. In this paper, according to the characteristic values of different equipment, big data technology is used to deeply mine the data, and the fault prediction model is built to realize the rapid fault location. This practice can ensure the normal operation of business, and can save the operation and maintenance cost of equipment.